Voting for Victors: Why Violent Actors Win Postwar Elections. (October 2019) - Daly, Sarah Zukerman
Abstract: Why do citizens elect political actors who have perpetrated violence against the civilian population? Despite their use of atrocities, political parties with deep roots in the belligerent organizations of the past win postwar democratic elections in countries around the world. This article uses new, cross-national data on postwar elections globally between 1970 and 2010, as well as voting, survey, archival, and interview data from El Salvador. It finds that belligerents' varied electoral success after wars can be explained not by their wartime levels of violence or use of electoral coercion, but by the distribution of military power at the end of conflict. It argues that militarily stronger belligerents are able to claim credit for peace, which translates into a reputation for competence on the provision of security. This enables them to own the security valence issue, which tends to crosscut cleavages, and to appeal to swing voters. The stronger belligerents' provision of security serves to offset and justify their use of atrocities, rendering their election rational. This article sheds light on political life after episodes of violence. It also contributes to understanding security voting and offers insights into why people vote in seemingly counterintuitive ways.